Influence of energy on the phase composition of the ultra-dispersed product of the molybdenum–carbon system obtained by the vacuumless arc discharge method; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 24, iss. 1 - Pak A. Ya. Aleksandr Yakovlevich (2020, 2020)
Title screen